Polyprenyl phloroglucinols and methyl esters of citric acid from the fruits of Garcinia multiflora - Nguyen Nghia Vu,; Hoang Thi Minh Nguyet,; Lo Van Nguyen,; Tran Thi Thu Thuy,; Giang, Phan Minh (Vietnam Journal of Science and Technology, 2023)
Garcinia multiflora belonging to the Clusiaceae family is one of the medicinal plant species native to Viet Nam and southern China and its use is an ethno-medicinal remedy to treat acne, scabies, constipation, and inflammation. The major bioactive classes of secondary metabolites were found in different parts of this plant such as phloroglucinol, xanthone, bioflavonoid, organic acid… In this paper, the chemical investigation on the fruits of Garcinia multiflora growing in the north of Vietnam was reported. Six compounds including two polyprenyl phloroglucinols (garcinol (1), isogarcinol (2)), one triterpene (friedelin (3)), and three methyl esters of citric acid (1,5,6-trimethyl citrate (4), 1,5-dimethyl citrate (5) and 6-methyl citrate (6)) were isolated from the methanol extract of fresh fruit pericarp using repeated column chromatography on different absorbents (silica gel, RP-18 and Sephadex). Their chemical structures were determined using spectroscopic methods (ESI-MS, 1D and 2D NMR) and comparison with the spectroscopic data in the literature. The absolute configurations of two polyprenyl phloroglucinols 1 and 2 were determined by comparison of its experimental optical rotation and NMR data with the reported values of their stereoisomers. This is the first report on the occurrence of the phytochemicals 1-6 in the fruits of Garcinia multiflora growing in Viet Nam.